Examining Asian parents’ perspectives and challenges in sexual and reproductive health education with implications for public health: a systematic review - Ellin, Mohammed Rasheedan; Abdul Hamid, Siti Hazariah; Mohd Arifin, Siti Roshaidai; Hasan, Haliza; Othman, Sajaratulnisah; Mohd Zain, Norhasmah (Wolters Kluwer Health, 2024)
In Asian cultures, discussing sexual matters with adolescents is often considered taboo and culturally or religiously sensitive. Due to a lack of knowledge and skills, many parents find approaching such a topic with their children challenging, fearing that raising such an issue will bring concerns about encouraging promiscuity. This systematic review aims to assess evidence on Asian parents’ perspectives and practices regarding delivering sexuality information to adolescents. It also seeks to identify the factors that facilitate or hinder the effective delivery of such knowledge. The electronic databases EBSCO-CINAHL, Scopus, and Science Direct were searched using keywords and synonyms such as “sexuality information,” “sexuality education,” “parent-child,” “communication,” and “Asian.” The studies’ quality was assessed using the Mixed-Method Assessment Tool. A comprehensive database search identified 1392 potentially relevant literature sources for this review. Following the application of inclusion criteria, a final set of 16 eligible full-text research articles was selected for inclusion in the review. In most quantitative literature, parents were found to have a good level of knowledge, whereas most qualitative studies reported the opposite, indicating inadequate knowledge. Seven studies highlighted the cultural denial of delivering regarding sexuality, whereas six studies emphasized the need for parental support. Negative experiences, including discomfort, shyness, embarrassment, fear of intimidation, and fearful encounters, were reported in the literature. In conclusion, this review aims to pinpoint gaps and challenges in the delivery of sexuality education among Asian parents, offering valuable insights for public health practitioners and policymakers.